A LEADERSHIP FUNCTIONS OF WOMEN BUREAUCRATS AS A LEADER IN A DENGUE FEVER DISEASE CONTROL IN THE DEPARTMENT OF HEALTH OF BEKASI CITY, WEST JAVA PROVINCE INDONESIA - Yuningsih, Neneng Yany (Advances in Social Sciences Research Journal, 2020)
The era of democracy has opened opportunities for women to have and build a career in various fields including in bureaucracy environment of civil apparatus. This research focuses on analyzing the role of leadership functions of women bureaucrats as a leader in dengue fever disease control in the Department of Health of Bekasi City in 2015-2016. Leadership theories are used to analyze the themes. During the period, dengue fever (DBD) disease is a disease with extraordinary status in Bekasi City; thus, it requires particular attention on its control from the municipal government of Bekasi City. The Department of Health of Bekasi City assigns dr. Pusporini as a person in charge to handle the DBD disease issue in the city. dr. Pusporini, as a bureaucrat, is a physician on duty in the department. She is the head of infectious disease control division. As a woman, it is not an easy task to be a leader with considerable responsibilities.